Respuestas

2014-02-05T01:50:22+01:00
A)
-2y=6x+12
   y=-3x - 6

-2y=6x+12
y= (6x+12) / -2         1)

y= -3x-6                  2)

sustituimos 2) en 1)

-3x-6= -3x-6
x*x= -3-6+3+6
x²= 0
x=√0
x=0

y= -3(0)-6
y= -6

b)
y=2x-1                       2)
   y=-4x + 11              1)

sustituir 2) en 1)

-4x+11=2x-1
+11+1=2x+4x
12=6x
12/6=x
2=x 

y=-4x+11
y=--4*(2)+11
y= 3

 
c) y=2x + 2         1)
   1/2y - 1= x       2)

despejar y en la 2ª ecuacion

1/2y-1=x
y=1/2x+1

sustituir 2 en 1

2x+2= 1/2x+1
2x-1/2x=1-2
3/2x=-1
x=-(1*2)/3
x= 2/3

y= 2*(2/3)+1
y= 4/3 +1
y= 7/3